Bytový dům ve Valašském Meziříčí - Pasztorek, Martin (Vysoké učení technické v Brně. Fakulta stavební)
Tato bakalářská práce se zabývá návrhem novostavby bytového domu. Navrhovaný bytový dům se nachází ve Zlínském kraji, ve městě Valašské Meziříčí. Navržený objekt obsahuje celkem 8 bytových jednotek. Objekt je částečně podsklepený a skládá se ze 4 nadzemních podlaží. V 1S se nachází skladovací sklepní kóje, technická a úklidová místnost. 1NP tvoří 3 samostatné úseky – kancelářský úsek, přístupový úsek k bytovým jednotkám s kočárkárnou a provozovna autoškoly. Tyto úseky jsou od sebe navzájem odděleny a každý úsek má vlastní přístupový vchod. Bytové jednotky se nacházejí v 2NP, 3NP a 4NP. 2NP tvoří malé byty – 3x 1+kk, 1x 1+1. Rozlohově větší byty se nacházejí ve 3NP a 4NP – 2x 3+kk, 2x 4+kk. Ke každé bytové jednotce náleží lodžie s výjimkou bytů ve 4NP – k těmto bytovým jednotkám náleží terasa nacházející se na ploché vegetační střeše. Bytový dům je vystavěn z keramických cihelných tvárnic a předstupující část je tvořena skeletovými prefabrikovanými prvky. Základová konstrukce se skládá ze základových pásů. Sloupy, které vynášejí převislou část, jsou uloženy na základových patkách. Suterénní zeď je vybudována z prefabrikovaných vylévaných betonových tvárnic. Stropní konstrukci tvoří předpjaté stropní panely Spiroll. Schodiště je železobetonové prefabrikované. Zastřešení řešeno plochou vegetační střechou. Zateplení objektu je řešeno vnějším kontaktním zateplovacím systémem, mezinárodně označovaný zkratkou ETICS. Jako tepelný izolant je použit expandovaný polystyren.

This Bachelor thesis deals with a design of new building – apartment house. Designed apartment house is located in Zlin region, in the town Valasske Mezirici. Altogether, the designed bulding contains partial basement, eight dwelling units and four storeys. In the ground floor we can find a storage cellar, utility room and cleaning room. The ground floor is made of 3 single sections – office section, section with access to dwelling units with the pram room and section with driving school. These sections are separated from each other and each section has its own entrance. Dwelling units are located on the second floor, third floor and fourth floor. The second floor is made of small flats – there are 3 studios and 1 one-room flat. Larger flats are located on the third and fourth floor where we can find 2 two-bedroom flats and 2 three-bedroom flats. Every dwelling unit has a disposal of the loggie except the flats on the fourth floor – these have a disposal of the terrace located on a flat green roof. Apartment house is built from clay block and overhang part is made of precast frame elements. Building foundations consist of foundation strips. The columns that are erecting the overhang part are placed on foundation pads. The basement wall is built from concrete blocks. Ceiling construction is made of prestressed ceiling panels Spiroll. Staircase is reinforced concrete precast. Roofing is solved by flat green roof. Thermal insulation of the building is solved by external contact insulation system that is internationally labeled and known as ETICS. As a thermal isolator serves the expanded polystyrene.
Residential building in Valašské Meziříčí
Keywords: Bytový dům; plochá vegetační střecha; autoškola; kanceláře; ETICS; Apartment house; flat green roof; driving school; offices; ETICS